AB0102 Differential Effects of CD4+T Cells and CD8+T Cells on the Induction of Osteoclasts from Human Monocytes. (10th June 2014) - Kondo, M.; Murakawa, Y.; Matsumura, T.; Moriyama, M.; Sumita, Y.; Harashima, N.; Harada, M.
Abstract : Background: Activated T cells express RANKL and have been considered to pomote osteoclast (OC) differentiation. Alternatively, activated T cells were suggested to suppress OC differentiation via the production of IL-4 and IL-10. Additionally, in a mouse model, activated T cells were reported to drive monocytes to differentiate into dendritic cells (DCs) through GM-CSF production. 1) Objectives: In this study, we investigated effects of CD4+ T cells or CD8+ T cells with or without IL-2 on the induction of OC from human monocytes. Methods: Monocytes, CD4+ T cells, and CD8+ T cells were prepared from PBMC of healthy volunteers. After incubation of monocytes with RANKL (50 ng/ml) and M-CSF (20 ng/ml) for 14 days, OC differentiation was evaluated by the TRAP staining. Additionally, we added CD4+T cells or CD8+T cells with or without IL-2 (20U/ml) at the initiation of the culture. Results: Apparent OCs were induced from human monocytes by the culture with RANKL and M-CSF. The addition of CD8+ T cells facilitated the OC differentiation. Conversely, the addition of CD4+ T cells with IL-2 remarkably inhibited the OC differentiation, with preferential induction of DCs. Conclusions: CD8+ T cells seem to facilitate OC differentiation from monocytes. Alternatively, irrespective of the presence of RANKL and M-CSF, CD4+ T cells with IL-2 facilitate DC differentiation, thereby resulting in drastic inhibition of OC differentiation. References: Miyamoto T, Ohneda O, Arai F, Iwamoto K, Okada S, Takagi K, et al. Bifurcation of osteoclasts and dendritic cells from common progenitors. Blood. 2001, 15;98(8):2544-54. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1416